Factors associated with adoption of coping strategies among Chinese patients with heart failure in ethnic minority regions. Issue 17 (24th January 2018) - Rong, Xiaoshan; Peng, Youqing; Yu, Haiping; Li, Dan
Abstract : Aims and objectives: To examine the coping strategies in patients with heart failure (HF) in the ethnic minority regions of China and to explore the factors affecting the adoption of coping strategies. Background: Effective coping with illness is an important element that influences the adaptation and increases the patient quality of life. Although different factors have been proposed to be determinants of coping strategy, findings are inconclusive, especially when it comes to the cultural background. Design: A cross‐sectional study was performed. Methods: A total of 360 HF patients in four districts of Xinjiang were enrolled. All participants completed the Medical Coping Modes Questionnaire, the Minnesota Living with HF Questionnaire and self‐management Questionnaire. Results: Heart failure patients had lower scores in confrontation and higher scores in avoidance and acceptance resignation than patients in the Chinese norm. The multiple regression analysis revealed several factors that indicate confrontation coping including symptom management, employment status and psychological and social management, whereas religion (R2), disease duration, employment status and payment system (P2) were identified as indicators of avoidance coping. In addition, ethnicity (E1), disease duration and employment status were indicators of acceptance resignation coping. Conclusions: Our findings from this study suggest that HF patients in the ethnic minority regions may use less confrontation coping and more avoidance and acceptance resignation coping than patients in the Chinese norm. Moreover, the cultural background, duration of disease, quality of life and self‐management play important roles in the selection of HF coping strategy. Relevance to clinical practice: The disparities of racial/ethnic exist in coping strategy. Healthcare providers are required to better understand the role of religion in the coping process and how it contributes to the selection of coping strategies.